Education Media Videos and Posters on Healthy Snacks Behavior In Elementary Schools Students - Mayasari, Eva; Hayu, Riska Epina; Permanasari, Ika (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Healthy food is food that contains substances needed by the body. Healthy foods contain balanced nutrition, which is food that is full of nutrients and is well consumed by the body. Media commonly used such as video media and posters, which are expected to help change student behavior. The design used in this study is quasi experiment with one pre-and post-village design. The results of the study obtained media health education through video and posters had a positive influence on knowledge (p = 0,000), attitude (p = 0.003), and actions (p = 0.002) of students in choosing healthy snacks. Students' knowledge before intervention is mostly in the good category and increases after being given health education through videos and posters. Media of health education through video and posters has a positive influence on the knowledge, attitudes and actions of students in choosing healthy snacks.